Follow-up tuberculosis prevalence survey of Transkei - Fourie, P B; Gatner, E M; Glatthaar, E; Kleeberg, H H (Tubercle, 1980)
After 5 years a follow-up prevalence survey was conducted in Transkei on a randomly selected sample of the rural population. The parameters investigated were bacteriological prevalence of tubercle bacilli in sputum, radiological prevalence of chest abnormalities associated with tuberculosis in adults, and hypersensitivity to tuberculin in children. Bacteriological positivity was 2.1% on smear microscopy and 4.3% on culture. Radiological evidence of tuberculosis was demonstrable in 12.5% of subjects, of whom 8.7% were considered active and 3.8% inactive. The mean prevalence of tuberculin positivity according to the Mantoux test was 30.1%. An annual risk of infection of 4% was calculated, showing a continuous decrease of 5% per year on the 7% risk of infection encountered in 1972. Compared with the first survey, a general reduction in prevalence of tuberculosis is evident.